Upaya Guru PAI Dalam Meningkatkan Kompetensi Pedagogik di Perguruan Tinggi Era Revolusi Industri 4.0 - Indra Prajoko (Edification Journal, 2021)
The rapid progress and development of technology and information in the era of the industrial revolution 4.0 has an impact in various fields, such as the impact in the economic, social, political, cultural and educational fields. In learning activities in the world of education, a very important role does not escape from a teacher / educator. Pedagogic competence is one of the concepts designed to be understood and mastered by educators as an important solution in dealing with the problem of Teaching and Learning Activities (KBM).